2023
DOI: 10.1002/nop2.1640
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between quality of discharge teaching, readiness for hospital discharge and health outcomes of hysterectomy patients: A structural equation model analysis

Abstract: Aim To explore the relationship between the quality of discharge teaching, readiness for hospital discharge and postdischarge health outcomes in hysterectomy patients. Design Cross‐sectional online survey. Methods A cross‐sectional survey design was used to investigate 331 hysterectomy patients in a hospital in Chengdu. The results were analysed using Spearman's correlation and structural equation model. Results Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…concluded that medical staff should conduct discharge training for hysterectomy patients according to their individual characteristics and needs and provide accurate, appropriate, standardized and e cient introductions and guidance. (25) The results of this study are the same regarding the age of most patients and companions. Also, in this study, the average score for the dimensions of the quality of the discharge process from the perspective of patients and companions showed that most of them needed to be taught the content received from the nurses at the time of discharge.…”
Section: Discussionmentioning
confidence: 67%
“…concluded that medical staff should conduct discharge training for hysterectomy patients according to their individual characteristics and needs and provide accurate, appropriate, standardized and e cient introductions and guidance. (25) The results of this study are the same regarding the age of most patients and companions. Also, in this study, the average score for the dimensions of the quality of the discharge process from the perspective of patients and companions showed that most of them needed to be taught the content received from the nurses at the time of discharge.…”
Section: Discussionmentioning
confidence: 67%